Assistance in preparation of PKM-K proposals (student creativity program-entrepreneurship) for Muhammadiyah University of Tasikmalaya students - Endah Nurmahmudah; Risa Nuryuniarti; Ida Herdiani; Dela Rahmah; Delita Nuraulia; Gea Mutiara Oktaviany (Universitas Muhammadiyah Magelang, 2023)
The Student Creativity Program (PKM) was held for the first time in 2011 until now, but apparently this activity has not become an annual culture for Muhammadiyah University of Tasikmalaya (UMTAS) students. Facing this reality, it is necessary to have a settlement solution so that the number of PKM proposals, especially in the field of entrepreneurship, can increase and be funded. The purpose of this community service program is to assist in the preparation of PKM-K proposals for UMTAS students using the pre-test and post-test methods, socializing PKM and PKMK, forming groups, searching for titles, making proposal templates, making proposal substance and completeness of attachments, as well as reviews, revisions, and evaluations. The results of this community service program were 32 PKMK proposals. The 32 proposals produced were very varied, the ideas and themes submitted were full of creations and innovations ranging from the food and beverage, trades, and services to the cultivation category. Proposals that have been prepared will be uploaded at the PKM 2023 event.